2021
DOI: 10.3390/foods10081904
|View full text |Cite
|
Sign up to set email alerts
|

Application of Raw and Defatted by Supercritical CO2 Hemp Seed Press-Cake and Sweet Grass Antioxidant Extract in Pork Burger Patties

Abstract: There is an increasing tendency toward the application of plant origin ingredients in meat products. This study evaluates the physicochemical properties and oxidative stability of pork burger patties produced with the addition of dried raw and defatted by supercritical CO2 extraction hemp seed press-cake as protein-rich ingredients (1.5–2.0%) and sweet grass ethanolic extract (0.5%) as a strong natural antioxidant. The main aim of using such a combination was to assess the possibility of mitigating the negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 45 publications
1
20
2
Order By: Relevance
“…The increase in PV and TBARS values indicate that the addition of hempseed cake accelerated the lipid oxidation in potato chips. This result is consistent with a previous study in which the addition of 1.5–2.0% hempseed cake increased the TBARS value and oxidation rate of pork patties [ 16 ]. In addition, Xiong, et al [ 58 ] added polyphenol-rich sorghum bran to beef sausages and observed the promoted lipid oxidation.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The increase in PV and TBARS values indicate that the addition of hempseed cake accelerated the lipid oxidation in potato chips. This result is consistent with a previous study in which the addition of 1.5–2.0% hempseed cake increased the TBARS value and oxidation rate of pork patties [ 16 ]. In addition, Xiong, et al [ 58 ] added polyphenol-rich sorghum bran to beef sausages and observed the promoted lipid oxidation.…”
Section: Resultssupporting
confidence: 93%
“…In order to inhibit lipid oxidation in potato chips, future research could focus on adding natural antioxidants to the product. For example, Kerner, Jõudu, Tänavots, and Venskutonis [ 16 ] added 0.5% sweetgrass ethanol extract as natural antioxidant to pork patties incorporated with raw hempseed, and they observed a positive effect on inhibiting lipid oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing consumer awareness of food quality, production trends, the relationship between diet and health, and lack of time are the most common reasons for introducing new, more nutritional products to the market, as well as easy-to-prepare meat products [ 1 , 2 , 3 ]. The addition of natural bioactive compounds to meat products is nowadays a popular trend in meat processing [ 4 , 5 , 6 ]. Currently, enriched meat products are obtained thanks to modification at the raw material production stage (appropriate selection of animal breed, in terms of the animal raw materials obtained) and selection and supplementation of feed [ 6 , 7 ], and enrichment of meat products at the processing stage.…”
Section: Introductionmentioning
confidence: 99%